2023
DOI: 10.1109/access.2023.3299171
|View full text |Cite
|
Sign up to set email alerts
|

Multistability and Bifurcation Analysis of a Novel 3D Jerk System: Electronic Circuit Design, FPGA Implementation, and Image Cryptography Scheme

Talal Bonny,
Sundarapandian Vaidyanathan,
Aceng Sambas
et al.

Abstract: In this paper, we propose a novel 3-D jerk system with three quadratic nonlinear terms and demonstrate the dynamical properties of the proposed jerk system in terms of phase portraits, bifurcation diagrams, Lyapunov exponents, multistability and coexisting attractors. For practical implementations, we apply Multisim version 14.0 to design an electronic model of the proposed 3-D jerk system. To demonstrate the feasibility of the proposed chaotic jerk system, we implement the system using a field-programmable ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In their work, conditions for the appearance of Hopf and fold bifurcations were constructed. A 3-D jerk system with three quadratic nonlinear terms was presented by Bonny et al [1], and the dynamical properties of the system were demonstrated by utilizing phase portraits, bifurcation diagrams, Lyapunov exponents, multistability, and coexisting attractors.…”
Section: Introductionmentioning
confidence: 99%
“…In their work, conditions for the appearance of Hopf and fold bifurcations were constructed. A 3-D jerk system with three quadratic nonlinear terms was presented by Bonny et al [1], and the dynamical properties of the system were demonstrated by utilizing phase portraits, bifurcation diagrams, Lyapunov exponents, multistability, and coexisting attractors.…”
Section: Introductionmentioning
confidence: 99%
“…Logistic map, Henon map, Henon 3-D map and Lorenz discrete map are discrete-time systems. In addition, the chaotic systems presented in previous work have been implemented using different techniques such as electronic circuits [ 13 , 14 ], FPGA implementation [ 15 18 ]and memristor-based circuits [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bonny et al in [13] have investigated a 3-D jerk system with three quadratic nonlinear terms. In their work, they studied the dynamical properties of the system using bifurcation diagrams, Lyapunov exponents, multistability and coexisting attractors.…”
Section: Introductionmentioning
confidence: 99%